ANALYZING PATIENT WAITING TIMES IN OUTPATIENT SERVICES: A MIXED-METHODS APPROACH TO OPTIMIZING HEALTHCARE DELIVERY AT KIEN AN HOSPITAL IN HAI PHONG CITY IN 2025 (Vietnam Journal of Community Medicine, 2026)
Background: Patient waiting time is a critical indicator of healthcare service quality that significantly influences patient satisfaction and healthcare outcomes. In Vietnam, extended waiting times remain a persistent challenge despite national regulatory frameworks established by the Ministry of Health. This study addresses a critical gap in understanding patient flow dynamics within provincial hospitals, contributing essential evidence to Vietnam's ongoing healthcare reform efforts aimed at service decentralization and quality improvement.Objective: This study aimed to assess patient waiting times at Kien An Hospital, identify factors influencing these durations, and develop evidence-based recommendations for service improvement that align with Vietnam's national healthcare transformation agenda.Methods: A mixed-methods approach combining quantitative and qualitative methodologies was employed. Quantitative data were collected from 250 outpatients through structured observation and questionnaires. Qualitative data was gathered through in-depth interviews with 15 participants. Analysis included descriptive statistics, comparative analysis, and thematic content analysis.Results: Patients experienced a mean waiting time of 172.05 ± 6.90 minutes, with diagnostic testing consuming the largest proportion (80.44 ± 4.25 minutes). Morning consultations required significantly longer waiting times than afternoon appointments (190.10 ± 8.03 versus 101.60 ± 6.47 minutes, p
Keywords: Patient waiting time, outpatient services, healthcare quality improvement, mixed-methods research, Vietnam healthcare system